2004
DOI: 10.1074/jbc.m311479200
|View full text |Cite
|
Sign up to set email alerts
|

The c-Abl Tyrosine Kinase Phosphorylates the Fe65 Adaptor Protein to Stimulate Fe65/Amyloid Precursor Protein Nuclear Signaling

Abstract: The amyloid precursor protein (APP) is proteolytically processed to release a C-terminal domain that signals to the nucleus to regulate transcription of responsive genes. The APP C terminus binds to a number of phosphotyrosine binding (PTB) domain proteins and one of these, Fe65, stimulates APP nuclear signaling. Fe65 is an adaptor protein that contains a number of protein-protein interaction domains. These include two PTB domains, the second of which binds APP, and a WW domain that binds proline-rich ligands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 50 publications
5
78
0
Order By: Relevance
“…5C). This is similar to previous observations in other cultured cell types (42). Dexras1 reduced the transcription further in both FE65 wild-type and FE65-Y547F co-transfected cells (Fig.…”
Section: Dexras1 and App Do Not Compete For Fe65 But Dexras1⅐ Fe65⅐asupporting
confidence: 81%
See 3 more Smart Citations
“…5C). This is similar to previous observations in other cultured cell types (42). Dexras1 reduced the transcription further in both FE65 wild-type and FE65-Y547F co-transfected cells (Fig.…”
Section: Dexras1 and App Do Not Compete For Fe65 But Dexras1⅐ Fe65⅐asupporting
confidence: 81%
“…FE65 and AICD have been shown to form a transcription stimulation complex for a GAL4-dependent reporter (3,42). In the present study, we have shown that Dexras1 binds to and co-localizes with FE65 in the nucleus.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The WW domain of FE65 binds the prolinecontaining motif of Mena, the mammalian homolog of enabled, which is involved in the control of cell motility through regulation of the actin cytoskeleton (16). Another ligand of the WW domain is the c-Abl tyrosine kinase, which phosphorylates APP on Tyr-682 (17,18) and Fe65 on Tyr-547, within the PTB2 domain (19). The member of INHAT complex SET/TAF1-b binds to a region of Fe65 overlapping the WW domain (20).…”
Section: The Adaptor Protein Fe65mentioning
confidence: 99%